Comparative evaluation of a hydrofoil-assisted trimaran - Moolman, Ryno (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2005.